Digital Platform Monetization in the Perspective of Christian Education: Integrating Work Values with Technology - Zalukhu, Amirrudin (STIPAK Malang, 2024)
The rapid growth of digital platform monetization has reshaped the global economy, providing individuals with new avenues for income generation and creative expression. However, these opportunities come with ethical dilemmas, such as content commodification, exploitation, and the erosion of personal authenticity. This study investigates digital monetization from the perspective of Christian education, emphasizing the integration of work values rooted in biblical principles, including diligence, integrity, stewardship, and service. Using a qualitative approach based on a comprehensive literature review, the research explores theological concepts of work, the role of Christian education, and case studies from monetized platforms such as TikTok and YouTube.The findings demonstrate that digital monetization can foster economic empowerment and innovation, but only when approached ethically. Christian education offers a robust framework for addressing these challenges by promoting moral discernment, digital literacy, and value-driven creativity. Through this lens, monetization can evolve into a means of service, community building, and stewardship, aligning with Christian principles.The study concludes with recommendations for educators, content creators, and policymakers to prioritize ethical standards and Christian work values in the digital economy. It suggests that future research focus on practical applications of these principles to ensure that technological advancements are leveraged responsibly in diverse sociocultural contexts.